Rekonstruksi Pembelajaran Perbankan Syariah Pada Perguruan Tinggi Islam - Juwita Anggraini Syahri; Maya Panorama (Jurnal Ilmiah Ekonomi Islam, 2020)
In the perception of the human capital of Islamic banking that is needed is (1) having good language skills and must be able to communicate effectively; (2) Banks demand human resources to be able to establish good cooperation, able to present material in public well and able to think critically; (3) Islamic banks also demand that human resources have good knowledge about contracts and transactions. This requires universities to carry out reconstruction of learning that is in line with Islamic banking needs. In this study found several steps in the reconstruction of banking learning including determining the achievement of banking learning, determining competencies, adjusting the curriculum, determining indicators of Islamic banking, media and learning methods and so forth.